Pengaruh Penerapan Hidroterapi Rendam Kaki Air Hangat terhadap Perubahan Tekanan Darah pada Lansia Hipertensi di RSUD Kota Salatiga - Novia Ariani; Erika Dewi Noorratri (Universitas Katolik Widya Karya Malang, 2023)
Hypertension is a health problem that is commonly found in the elderly. The number of people with hypertension continues to increase every year, it is estimated that by 2025 there will be 1.5 billion people affected by hypertension. Hypertension can occur due to various factors, namely: unhealthy diet / diet, smoking lifestyle and alcohol consumption, obesity or excessive weight, lack of exercise / physical activity, excessive salt intake, consumption of saturated fat, use of estrogen, lack of fruit and vegetable intake. Efforts to overcome hypertension can be done with pharmacological and non-pharmacological therapies . Non-pharmacological therapies can be done by modifying lifestyle, complementary therapies such as; hydrotherapy (foot bath) and physical exercise. In the Nursing Interventions Classification (NIC) warm water foot soak is one of the interventions of nursing diagnosis, namely peripheral tissue perfusion disorders. Descriptive research using case study design. There was a decrease in blood pressure in hypertensive elderly after hydrotherapy soaked feet warm water. There are differences in the development of lowering blood pressure in hypertensive elderly before and after hydrotherapy soak feet warm water.